2001
DOI: 10.1002/mrd.1098
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transfer in cattle with non‐transfected and transfected fetal or cloned transgenic fetal and postnatal fibroblasts

Abstract: The efficiency of nuclear transfer (NT) using two primary cultures of fetal fibroblasts (FF1 and FF2) was compared vs. the same cultures transfected with an expression vector in which the bovine prochymosin coding sequence is placed under the control of the bovine alpha(S1)-casein promoter (TFF1 and TFF2). In addition, fibroblasts of a cloned transgenic fetus (TRFF1) derived from TFF1 and ear skin fibroblasts of a 1-month-old cloned transgenic calf (TRCF1) derived from TRFF1 were used as nuclear donors. Embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 30 publications
2
53
1
1
Order By: Relevance
“…Iguma et al [25], Forsberg et al [26] and Zakhartchenko et al [27] reported that in the case of cattle, genetic modification of donor cells influences the number of cloned calves born. An increase in chromosomal aberration, such as mutation and deletion due to a long culturing period, is considered one of the causes.…”
Section: Discussionmentioning
confidence: 99%
“…Iguma et al [25], Forsberg et al [26] and Zakhartchenko et al [27] reported that in the case of cattle, genetic modification of donor cells influences the number of cloned calves born. An increase in chromosomal aberration, such as mutation and deletion due to a long culturing period, is considered one of the causes.…”
Section: Discussionmentioning
confidence: 99%
“…47 However, somatic cells have a limited life span in in vitro culture, and the decrease in developmental rates for modified cells has been attributed to the extended culture periods associated with the transfection and selection procedures before SCNT. 48 Studies using different approaches aimed at increasing the efficiency for the generation of viable clones have been performed. The methods investigated include recloning, autologous SCNT, impeding Xist expression from the active X chromosome, treatment with trichostatin A after SCNT and histone deacetylase inhibitors, among others.…”
Section: Strategies For the Generation Of Transgenic Cattlechallengesmentioning
confidence: 99%
“…The integrated gene can be examined before proceeding to nuclear transfer. This method is without contest more attractive than microinjection for sheep [35], goats [19,32] and cows [2,43].…”
Section: Gene Additionmentioning
confidence: 99%